Zwitterion Effect of Cow Brain Protein towards Efficiency Improvement of Dye-Sensitized Solar Cell (DSSC) - Denny Widhiyanuriyawan; Prihanto Trihutomo; Sudjito Soeparman; Lilis Yuliati (The Scientific World Journal)
Dye-Sensitized Solar Cell (DSSC) constitutes a solar cell using natural dyes from plants that are adsorbed in semiconductors to convert solar energy into electrical energy. DSSC has relatively inexpensive fabrication costs, is easy to produce, works in visible light, and is environmentally friendly. The disadvantage of DSSC is that its efficiency is still low compared to silicon solar cells. This low efficiency is due to obstacles in the flow of electric current on DSSC. In this study, DSSC has been successfully fabricated with the deposition of clathrin protein from cow brain. The zwitterions effect of protein on cow brain is able to reduce resistance and increase electric current on DSSC. The zwitterions effect of cow brain protein that fills gaps or empty spaces between TiO2 particles generates acidic reactions (capturing electrons) and bases (releasing electrons); hence, proteins in the cow brain are able to function as electron bridges between TiO2 molecules and generate an increase in electric current in DSSC. The method used in this research was to deposit clathrin protein from cow brain in a porous TiO2 semiconductor with a concentration of 0%, 25%, 50%, and 75%. Tests carried out on DSSC that have been performed were X-Ray Diffractometer (XRD) testing to determine the crystal structure formed, Fourier Transform Infrared Spectroscopy (FTIR) testing to determine the functional groups formed on DSSC, Scanning Electron Microscopy (SEM) testing to determine the surface morphological characteristics of the DSSC layer, and testing the efficiency using AM 1.5 G solar simulator (1000 W/m2) to determine the efficiency changes that occur in DSSC. From the XRD test results by increasing the concentration of cow brain protein in DSSC, the structure of amino acid crystals also increased and the crystal size increased with the largest crystal size of 42.25 nm at the addition of 75% of cow brain protein. FTIR test results show that the addition of cow brain protein will form functional protein-forming amino groups on DSSC. FTIR analysis shows the sharp absorption of energy by protein functional groups in the FTIR spectrum with increasing concentration of cow brain protein in DSSC. The SEM test results show that the concentration of additional molecules of protein deposited into TiO2 increases and the cavity or pore between the TiO2 molecules decreases. The reduction of cavities in the layers indicates that protein molecules fill cavities that exist between TiO2 molecules. From the results of testing using AM 1.5 G solar simulator (1000 W/m2), the highest efficiency value is 1.465% with the addition of 75% brain protein concentration.